Update on the bird-egg syndrome and genuine poultry meat allergy - Hemmer, Wolfgang (Allergo J Int, 2016)
Allergy to poultry meat is rare and affects both children and adults. The prevalence of poultry meat allergy is unknown, but presumably is similar to that of red meat allergy. There is no close relationship between allergy to poultry meat and allergy to red meat. Poultry meat allergy may present as primary (genuine) food allergy or as secondary food allergy resulting from cross-reactivity. Secondary poultry meat allergy may arise in the context of bird-egg-syndrome, which is due to sensitization to serum albumins present in many tissues including muscle tissue and egg yolk (Gal d 5). Primary sensitization to serum albumin may happen via the respiratory tract through exposure to pet birds (mainly in adults) or within the context of egg allergy in early childhood. Due to the heat lability of serum albumins, reactions are often limited to the skin upon contact with raw meat. Symptoms from meat ingestion are rare and mostly mild, whereas systemic reactions are common after ingestion of raw or soft-boiled egg yolk. Primary poultry meat allergy is mainly seen in adolescents and young adults, though hypersensitivity may have started already at (pre)school age. Egg allergy is usually absent. Typical symptoms of primary poultry meat allergy include OAS (±dyspnea), gastrointestinal complaints, urticaria and angioedema. Severe anaphylaxis with cardiovascular symptoms is rare. Chicken and turkey meat are highly cross-reactive and responsible for most reactions, while duck and goose meat causes milder or no symptoms. Soups, sausages, and ham represent relevant allergen sources, too. Patients with poultry meat allergy unexpectedly often suffer from concomitant allergy to fish and possibly shrimp. Serum specific IgE against fish and shrimp is found in respectively 60 and 40 % of sera, suggestive of cross-reactive allergens in these foods. The allergens thus far recognized in genuine poultry meat are LMW proteins of 5–25 kDa. One of them has been identified as α-parvalbumin cross-reactive with homologous mammal α-parvalbumins but not with fish α-parvalbumins. Recently, myosin light chains, including 23 kDa MLC-1 (Gal d 7) and 15 kDa MLC-3, have been recognized as new major allergens in chicken meat. The high similarity of chicken MLCs with those from various fish species (∼65 %) might explain the clinical association of poultry meat allergy with fish allergy.